High-density thermoplastic vulcanizates based on LLDPE/NR for truck ﬂoor mats application - Dwi Wahini Nurhajati; Umi Reza Lestari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2021)
The use of thermoplastic vulcanizates (TPVs) that was obtained from a blend of thermoplastics and natural rubbers are considered suitable for the automotive applications purpose. To modify the performance of TPVs to a high density TPVs, the high density filler such as bismuth oxide (Bi₂O₃) was added. The focus of this study was on the development of a high density TPVs based on linear low density polyethylene (LLDPE)/natural rubber (NR) blend with different proportions of Bi₂O₃ filler that meets with requirements for truck floor mats materials. The high density TPVs were prepared by melt blending in a Kneader. Bismuth oxide filler loading was varied by 50; 150; 200; 250 phr and 300 phr. An increase in the weight load of bismuth oxide in TPVs increase density, hardness, and volume loss but reduce the tensile properties, tearing strength, and burning rate of high density TPVs. The test results showed that the TPVs containing 250 phr Bi₂O₃ was a promising candidate for use as a truck floor base.